Pengaruh Komunikasi Verbal Orangtua Terhadap Perilaku Sosial Siswa di SMP Muhammadiyah Kecamatan Singkut - Sri Wahyu; Rasimin Rasimin; Siti Amanah (Journal on Education, 2023)
Verbal communication that is carried out by parents and children is communication that always occurs and is established, especially with the mother, from the time the child is in the womb until the child is born and develops into adulthood, the child always makes contact and talks with his mother and father. From the results of observations and interviews on Monday 18 January 2021 at the Muhammadiyah Junior High School in Singkut District, there are many students who tend to socialize in groups and often have friends they don't like to hang out with, thus making researchers feel interested in taking up this research. The type taken in this study is quantitative research, namely systematic scientific research on parts and phenomena as well as the causality of relationships. This study uses a survey method. This research is ex post facto research. The number of samples in this study is 198 samples. Based on the results of the study for parents' verbal communication questionnaire data with a sample of 189 people, an average value of 123.8360 was obtained and a standard deviation of 12.58332, the highest value obtained was 150 and the lowest was 89. For social behavior questionnaire data of students with a sample of 189 people, it was obtained the average value is 129.0317 and the standard deviation is 15.59900, the highest value obtained is 155 and the lowest is 79, for the variable Family Harmony (X) of 0.847 or it can be expressed as a linear equation Y = 29.435 + 3.230 X. In the table the values ​​for the test two parties t 0.95 = 1.612 It is easy to see that 27.8834 > 1.6612, the parental verbal communication variable influences students' social behavior. the R value is the correlation found to be 0.907 and the R square is worth 0.823 or (82.4%) this shows that the percentage of the influence of the independent variable (X) on the dependent variable (Y) is 82.3%, while 17.7% is influenced or clarified by other variables not included in this research model. The conclusion of this study is that parents' verbal communication with a percentage of 2.60% is in the high classification or can be said to be good. The social behavior of students at SMP Muhammadiyah Singkut District with a percentage of 83.25% is high or can be said to be good. Based on the results of the study that there is an influence of parental verbal communication on the social behavior of students at SMP Muhammadiyah Singkut District and the influence of variable X on variable Y by looking at the determination index of 0.823% or it can be interpreted as strong.